Myopia Control With Multifocal Lens in School-Aged Children: A Meta-Analysis - Chen, Meilan; Xu, Lu; Li, Hongyang; Cai, Fengping; Wang, Hao; Hu, Chun; Wu, Yi (Frontiers in Pediatrics, 2022)
Background Myopia is one of the most common eye diseases in school-aged children. Multifocal lens (MFL) is one of the interventions that has being widely applied to control the progress of myopia. However, the treatment effects of MFLs in school-aged children require to be systematically evaluated. Methods A systematic analysis on qualified randomized controlled trials (RCTs) in which MFLs were prescribed as the intervention and single-vision lenses (SVLs) as the control was conducted. The treatment effects referring to the mean differences in spherical equivalent refraction (SER) and axial length (AL) between MFLs and SVLs groups were analyzed. Results With annual visit (3-years follow-up), the weighted mean differences (WMDs) in SER between MFLs and SVLs were 0.29 D (95% CI, 0.21 ∼ 0.37, p < 0.00001), 0.46 D (95% CI, 0.32 ∼ 0.60, p < 0.00001), and 0.64 D (95% CI, 0.40 ∼ 0.88, p < 0.00001) at the first, second, and third year; in AL were −0.12 mm (95% CI, −0.14 ∼−0.11, p < 0.00001), −0.19 mm (95% CI, −0.22 ∼−0.16, p < 0.00001), and −0.26 mm (95% CI, −0.31 ∼−0.21, p < 0.00001) at the first, second, and third year. With 6-months interval trials (2-years follow-up), the WMDs in SER from MFLs were 0.14 D (95% CI, 0.08 ∼ 0.20, p < 0.0001), 0.19 D (95% CI, 0.11 ∼ 0.28, p < 0.0001), 0.24 D (95% CI, 0.16 ∼ 0.33, p < 0.0001), 0.31 D (95% CI, 0.18 ∼ 0.44, p < 0.0001) and in AL from MFLs were −0.08 mm (95% CI, −0.09 ∼−0.07, p < 0.00001), −0.10 mm (95% CI, −0.12 ∼−0.09, p < 0.00001), −0.14 mm (95% CI, −0.17 ∼−0.11, p < 0.00001), and −0.18 mm (95% CI, −0.22 ∼−0.14, p < 0.00001) slower comparing with SVLs at follow up of 6, 12, 18, and 24 months, respectively. Conclusion The treatment effects of MFLs to slow down the myopic progress are positive in both 6-months and annual-visit trials and which could be sustained till 36 months. While a slight weaker treatment effect was observed after the first visit in 6-months visit, a slight rebound was observed at the following visit points. Furthermore, the treatment effects in annual visit are more profound than 6-months visit at almost all stages especially in SER. Our analysis encourages the MFLs users to maintain a long-term treatment with annual visit.